Retrospective analysis of outcomes in patients with myocardial infarction in late admission to PCI center - S. A. Vorontsova; T. V. Pavlova; A. A. Avramenko; S. M. Khokhlunov (Российский кардиологический журнал)
Aim. This study aims to determine the impact of invasive treatment strategy on long-term outcomes in patients with ST-segment elevation myocardial infarction (STEMI) in late admission to PCI center (12-48 hours from the symptom onset) in comparison with conservative management.Material and methods. The study population included 154 people with STEMI, admitted to V. P. Polyakov Samara Regional Clinical Cardiology Dispensary during 12-48 hours after onset of myocardial ischemia symptoms, for the period of inclusion (2013-2017). The mean age of the patients was 57,2±9,2 years old. The study evaluated two time periods: intrahospital and long-term (during 4 years from the index hospitalization). The primary end-point: cardiovascular death. The secondary combined end-point included: myocardial infarction recurrence, life-threatening rhythm disturbances, acute bleeding, heart failure NYHA III-IV functional class. The patients were divided into two groups depending on initially chosen management strategy: invasive (I) (n=113; 73,4%) or conservative (II) treatment (n=41; 26,6%).Results. Comparing frequency of occurrence of cardiovascular death depending on chosen treatment tactics, we found that the probability of lethal outcome from cardiovascular causes in conservatively treated patients increased by 20,64 times (95% confidence interval (CI): 1,04-408,61), p=0,018 during intrahospital period of the study. The analysis performed using the Kaplan-Meier method showed the medians of the time of lethal outcome occurrence: in conservative group — 76,5 months (95% CI: 67,6-85 months), in invasive group — 92,1 months (95% CI: 88,9-95,3 months), p=0,014.Conclusion. This study presented the results of our own retrospective study which confirms that revascularization in late-presenting patients with STEMI (12-48 hours from the symptom onset) results in improving the outcomes in both intrahospital and long-term periods.